Transformasi peta unit model (suatu prosedur alternatif pada pemetaan secara fotogrametris) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT In photogrammetric mapping model restitution is usually executed after aerial triangulation process. This procedure causes dependency of model restitution. The development of analytical stereoplotter and semi analytical stereoplotter provides a feasibility to process both steps simultaneously. This investigation tries to evaluate an alternative procedure by taking a pair of overlapping photographs. The result shows that this new alternative gives an adequate result for the flat area on 1:2000 scale